TRADITIONAL HEALTH CARE POLICY INSTRUMENTS TO SUPPORT THE PUBLIC HEALTH LEVEL OF SURABAYA CITY - Lilik Pudjiastuti (Jurnal Dinamika Hukum, 2016)
Traditional health care is one of the health care practices which grows in society. In addition, the existence of traditional practice is legally acknowledged by the Government Regulation No 103 of 2014 on Traditional Health Care. In its implementation of health development, the traditional health care must be reliable, secure and in accordance with religious and social culture norms.In traditional health care, there are some law-violating issues as well as  the lack of public knowledge. Thus, in order to guarantee the quality of traditional health care and improve public health level, the government shall make policy in order to control the traditional health care. The policy can be in the form of laws, license, control and law enforcement. The government policy in order to guarantee the quality of traditional health care is the realization of state responsibility as stated in Article 28 H sub article 1 and Article 28 I sub article 4 of the 1945 Constitution. Keywords: Policy, Traditional Health Care, Law Enforcement